The climate crisis and the ways of response - Ivanova, Zinaida (project baikal, 2023)
The article raises questions about the climate crisis, which manifests itself in global warming, emergencies that pose a danger to cities and towns, buildings, structures, and people’s health. The author presents different points of view on climate change, the role of greenhouse gases and the anthropogenic contribution to global warming. A study was made of the proposed ways of adapting construction and architecture to the situation of global warming, mitigating the negative effects of climate change. The author highlights topical areas of scientific research, such as: the formation of carbon-neutral architecture, the development of bioengineered building materials, the creation of “vertical gardens”, etc. The author presents the results of a sociological survey of the students of National Research Moscow State University of Civil Engineering of the year 2021-2022. The results are showing their understanding of the causes of climate change, professional responsibility and readiness to counteract the negative effects of climate change.